Understanding the Link Between Allergy and Neurodevelopmental Disorders: A Current Review of Factors and Mechanisms - Chua, Regena Xin Yi; Tay, Michelle Jia Yu; Ooi, Delicia Shu Qin; Siah, Kewin Tien Ho; Tham, Elizabeth Huiwen; Shek, Lynette Pei-Chi; Meaney, Michael J.; Broekman, Birit F. P.; Loo, Evelyn Xiu Ling (Frontiers in Neurology, 2021)
Both allergic diseases and neurodevelopmental disorders are non-communicable diseases (NCDs) that not only impact on the quality of life and but also result in substantial economic burden. Immune dysregulation and inflammation are typical hallmarks in both allergic and neurodevelopmental disorders, suggesting converging pathophysiology. Epidemiological studies provided convincing evidence for the link between allergy and neurodevelopmental diseases such as attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Possible factors influencing the development of these disorders include maternal depression and anxiety, gestational diabetes mellitus, maternal allergic status, diet, exposure to environmental pollutants, microbiome dysbiosis and sleep disturbances that occur early in life. Moreover, apart from inflammation, epigenetics, gene expression and mitochondrial dysfunction have emerged as possible underlying mechanisms in the pathogenesis of these conditions. The exploration and understanding of these shared factors and possible mechanisms may enable us to elucidate the link in the comorbidity.